Prevalência e fatores associados ao consumo de tabaco entre estudantes do interior do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
The aim of his survey was to determine the prevalence of the use of tobacco and to identify associated factors among elementary and high school students in a sample of public schools in 18 inland cities of the Amazon State, Brazil, between 2004 and 2006. This is a quantitative cross-sectional study using an standard anonymous self-administered questionnaire, of collective application. The sample consisted of 11,075 students. For the statistical analysis, univariate analysis was used to describe the variables studied, bivariate analysis was used to verify the association between those variables and the lifetime use of tobacco with chi-square test and Fisher s exact test, and the multivariate analysis using the logistic regression analysis was utilized to identify the main factors that influenced the frequent use of tobacco by the students. Lifetime tobacco use was reported by 35.62% students, more frequently by males (44.19%), of evening courses (38.91%), with remunerated jobs (42.94%), with results statistically significant. The frequent use of tobacco was mainly associated with males, remunerated Jobs, being in high school, on evening courses, with one year or more of school failure, live with smokers. Despite regional characteristics the results of prevalence for lifetime use of tobacco are similar to the national data in other studies. The data of the multivariate analysis allowed to know about the most important factors for the frequent use of tobacco among these students, and this information is useful to prevention actions over this population.
Keywords: Tabagismo - Manaus; Saúde de adolescentes; Saúde escolar; Tobacco; CIÊNCIAS DA SAÚDE: SAÚDE COLETIVA